A Comparative Analysis of Imprisonment and Fine Sanctions under the Indonesian Criminal Code and the Wetboek van Strafrecht (WvS) for the Criminal Offense of Fraud - Tiara Lala; Farhana Farhana (Fakultas Syariah IAIN Langsa, 2026)
Ideally, sanctions for the offense of fraud should be formulated proportionally by taking into account the objectives of punishment, including retribution, deterrence, offender rehabilitation, public protection, and the restoration of victims' losses. However, in practice, the Wetboek van Strafrecht (WvS) continues to treat imprisonment as the primary sanction without providing adequate room for fines as an alternative punishment better suited to the nature of economic crimes. This study aims to comparatively analyze the regulation of imprisonment and fines for fraud under the Indonesian Criminal Code (KUHP) and the Wetboek van Strafrecht (WvS), as well as to assess their conformity with the objectives of punishment. This research employs a normative legal method using statutory and comparative approaches through the analysis of primary and secondary legal materials. The findings reveal that the Indonesian Criminal Code adopts a more modern and proportionate sentencing approach by providing fines as an alternative to imprisonment, whereas the Wetboek van Strafrecht remains oriented toward imprisonment as the principal form of punishment. Therefore, the Indonesian Criminal Code is considered more consistent with contemporary sentencing objectives because it emphasizes a balance between justice, legal certainty, legal utility, and the restoration of victims' losses.